The Effect Of Work Productivity And Career Development On Employee Commitment At Pt. Mitsubishi Ocean Berlian Main Motorcycle, Bengkulu City - Reni Indriani; Egi Putra Utama (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of work productivity and career development on employee commitment at PT. Mitsubishi Lautan Berlian Utama Motor Bengkulu City. This research was conducted on employees of PT. Mitsubishi Lautan Berlian Utama Motor Bengkulu City, the population used in this study were 40 employees. The number of samples in this study were 40 people. The data that has been collected is processed using the Multiple Linear Regression Analysis Test technique, and the Hypothesis Test, namely the t test and f test. From the results of this study it can be concluded that partially the Work Productivity variable has a significant effect on the Commitment variable, H1 is accepted, and the Work Development variable has a significant effect on the Commitment variable, H1 is accepted, while the f test Work Productivity and Career Development jointly have a significant effect on Commitment Employees at PT. Mitsubishi Lautan Berlian Utama Motor Bengkulu City. So that H3 is accepted. The overall significant level is (Sig. a = 0.000 <0.05). As well as having a regression equation Y = 1,320 + 0.256X1 + 0.269X2 and the coefficient of determination R2, the Adjust R Square value is 0.652. The most dominant factor with the greatest regression coefficient value is the Career Development variable (X2) with a value of 0.269